Simultaneous determination of clobutinol hydrochloride and doxylamine succinate from syrups by RP HPLC using a new stationary phase containing embedded urea polar groups - Paulo Cesar Pires Rosa; Isabel Cristina Sales Fontes Jardim (Universidade de São Paulo, 2012)
A new, simple, fast, reproducible and sensitive reversed phase HPLC method, using a new stationary phase containing embedded urea polar groups, has been developed and validated for the simultaneous determination of clobutinol hydrochloride (CLO) and doxylamine succinate (DOX) in syrups. The determination was carried out on a C8 urea column (125 mm x 3.9 mm i.d., 5 µm particle size) synthetized at the Liquid Chomatography Laboratory (LabCrom) of the Chemistry Institute of Unicamp. The mobile phase consisted of a mixture of acetonitrile:methanol:phosphate buffer (pH 2.5) in the gradient mode. The diode array detector (DAD) was operated at 230 nm for CLO and 262 nm for DOX. The method showed adequate precision, with relative standard deviations (RSD) less than 1%. The presence of the excipients did not interfere in the results of the analysis. Accuracy was determined by adding standards of the drugs to a placebo and good recovery values were obtained. The analytical curves were linear (r² 0.9999 for CLO and 0.9998 for DOX) over a wide concentration range (2.4-336 µg mL-1 for CLO and 2.3-63 µg mL-1 for DOX). The solutions were stable for at least 72 hours at room temperature. The criteria for validation using the ICH guidelines were fulfilled. Um novo método simples, fácil e reprodutível, de fase reversa para CLAE, usando uma fase estacionária contendo um grupo polar, uréia, embutido, foi desenvolvido e validado para determinação simultânea de cloridrato de clobutinol (CLO) e succinato de doxilamina (DOX) em xarope. A determinação foi realizada em uma coluna C8 uréia (125 mm x 3,9 mm d.i., 5 µm tamanho de partícula) sintetizada em nosso laboratório (LabCrom). A fase móvel consistiu de mistura de acetonitrila:metanol:tampão fosfato pH 2,5, em eluição por gradiente. O detector por arranjos de diodo (DAD) foi utilizado a 230 nm para CLO e a 262 nm para DOX. O método apresentou precisão adequada, com desvio padrão relativo menor que 1%. A presença de excipientes não interferiu nos resultados obtidos. A exatidão foi realizada pela adição dos padrões dos fármacos ao placebo e valores de recuperação aceitáveis foram obtidos. As curvas analíticas mostraram-se lineares (r² 0,9999 para CLO e 0,9998 para DOX) em uma ampla faixa de concentração (2,4-336 µg mL-1 para CLO e 2,3-63 µg mL-1 para DOX). A solução padrão foi estável por 72 horas a temperatura ambiente. Os parâmetros de validação foram realizados conforme o guia ICH.